The effect of consumption Ziziphus jujuba on metabolic factors: A systematic review and meta-analysis of randomized clinical trials - Azadeh Heydarian; Negin Tahvilian; Hossein Shahinfar; Seyed Ali Abbas-Hashemi; Hossein Bahari; Sahar Cheshmeh; Naheed Aryaeian (Clinical Nutrition Open Science, 2024)
Summary: Purpose: Previous studies have reported that Ziziphus jujuba has beneficial effects on wellness, including antioxidant and anti-inflammatory properties, as well as improving the lipid profile. However, the evidence in this field is unclear. The current systematic study and meta-analysis aim to investigate the effect of Ziziphus jujuba on metabolic factors, including BMI, FBG, TG, TC, LDL, and HDL. Methods: We searched for randomized clinical trials on online resources such as PubMed, Scopus, and ISI Web of Science until October 2022. Four eligible articles were included in the current investigation. Results: The results of the current research revealed that the consumption of Ziziphus jujuba significantly reduces BMI (WMD: -1.03 kg/m2; 95% CI, -1.77 to -0.29, p=0.006), TG (WMD: -24.64 mg/dl; 95% CI, -33.64 to -15.64, p<0.001), TC (WMD: -12.43 mg/dl; 95% CI, -17.51 to -7.35, p<0.001) LDL (WMD: -6.96 mg/dl; 95% CI, -10.84 to -3.09, p<0.001). However, FBG (WMD: 0.94 mg/dl; 95% CI, -1.48 to 3.37, p=0.446) and HDL WMD: -0.58 mg/dl; 95% CI, -1.85 to 0.69, p=0.369) did not have significant changes. Conclusion: The findings of this research demonstrated that Ziziphus jujuba consumption may help improve the number of metabolic indicators. However, the findings of the current study should be interpreted with caution, given the paucity of investigations in this field and the need for more randomized clinical trial studies.